2015
DOI: 10.1111/srt.12210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of light‐emitting diodes (LED) effect on skin biology (in vitro study)

Abstract: These benefits may lead to reinforcement of the skin organization and structure. This hypothesis will be checked in future clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The latter system directly measured the local TEP by setting the potential reference right under the measuring point, minimizing the influence of surrounding tissue like dermis and hypodermis. From the similarity between the results of these two systems, the direct effect of the dermis on the measured TEP in the present experiments is negligibly small, although dermal fibroblasts have been reported to respond to light stimuli [6]. Since the promotion effect was not observed by the blue / purple irradiations ( Fig 2C ), it could be concluded that the wavelength of the red light (> 600 nm) is beneficial for the recovery of skin barriers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The latter system directly measured the local TEP by setting the potential reference right under the measuring point, minimizing the influence of surrounding tissue like dermis and hypodermis. From the similarity between the results of these two systems, the direct effect of the dermis on the measured TEP in the present experiments is negligibly small, although dermal fibroblasts have been reported to respond to light stimuli [6]. Since the promotion effect was not observed by the blue / purple irradiations ( Fig 2C ), it could be concluded that the wavelength of the red light (> 600 nm) is beneficial for the recovery of skin barriers.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, uses of LED on skin care shows promising results [4], in addition to promoting the recovery of damaged epidermal barrier [5]. Studies on photochemical responses of skin have revealed that the photo-activated mitochondrial function improved the morphology and proliferation of epidermal cells [6]. Interestingly, the expression of a photoreceptor-like proteins in epidermal cells has been reported [7].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, red-LEDs have been handled in clinics and scienti c researches [22], but the information for the use of blue, green, and orange-LEDs are limited. Even so, it is known that low energy blue, green, and orange LEDs can promote several biological effects on the tissue and cellular levels [16,17,22]. Thus, it was stated that orange light can be a promising wavelength to combat skin aging [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the biostimulation effect of different wavelengths emitted from these light sources is considerably known, it is still necessary to design a more e cient system to illuminate the cells for the investigation of the underlying mechanism of photobiomodulation. The main problem in these applications is that there is an energy loss during irradiation with the existing light systems [3,10,16,17]. In this study, we aimed to design and produce a portable LED-based photobiomodulation system that ts 12-well cell culture plates and works as a cover for those plates.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of publications have already demonstrated the clinical benefits of photobiomodulation [5, 6]. We choose to explore the combined effect of light and active ingredients by systematic in vitro and ex vivo studies and measure the cellular and molecular changes on skin cell populations [7] before assessing clinical safety and relevance of our results.…”
Section: Introductionmentioning
confidence: 99%